Social Work in the Asia Pacific Region in the 21 st Century: Challenges, Opportunities and the Role for Social Work Education - David Rose (Indonesian Social Work Consortium (ISWC), 2024)
The recent pandemic is an example of the major global challenges that impact locally and globally including war and conflicts, climate change, ecological damage, human and natural disasters, gender-based inequality and violence, poverty and inequality, and global movements of peoples. The Asia Pacific Region incorporates a vast geographic area of the world with a diverse range of countries at various stages of social and economic development, but all of which share the impacts of many of these global challenges. Social workers are a key workforce that can contribute to social development and work at the interface of the local with the global across the region. Drawing on literature, policy documents and observations some of the current challenges facing the development of the social work workforce in the region will be discussed as well as the opportunities for social work to contribute to social development and to the achievement of the UN Sustainable Development Goals. The critical role of social work education in developing the social work workforce to meet these global challenges is also discussed.